Maintenance of species boundaries in a Neotropical radiation of Begonia. Issue 19 (28th September 2015) - Twyford, Alex D.; Kidner, Catherine A.; Ennos, Richard A.
Abstract A major goal of evolutionary biology is to determine the mechanisms generating biodiversity. In Begonia, one of the largest plant genera (1900+ species), it has been postulated that the high number of endemic species is a by‐product of low gene flow among populations, which predisposes the group to speciation. However, this model of divergence requires that reproductive barriers accumulate rapidly among diverging species that overlap in their geographic ranges, otherwise speciation will be opposed by homogenizing gene flow in zones of secondary contact. Here, we test the outcomes of secondary contact in Begonia by genotyping multiple sympatric sites with 12 nuclear and seven plastid loci. We show that three sites of secondary contact between B. heracleifolia and B. nelumbiifolia are highly structured, mostly containing parental genotypes, with few F1 hybrids. A sympatric site between B. heracleifolia and B. sericoneura contains a higher proportion of F1s, but little evidence of introgression. The lack of later‐generation hybrids contrasts with that documented in many other plant taxa, where introgression is extensive. Our results, in conjunction with previous genetic work, show that Begonia demonstrate properties making them exceptionally prone to speciation, at multiple stages along the divergence continuum. Not only are populations weakly connected by gene flow, promoting allopatric speciation, but species often show strong reproductive barriers in secondary contact. Whether similar mechanisms contribute to diversification in other large genera remains to be tested.